2017
DOI: 10.3389/fnhum.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

Concealed, Unobtrusive Ear-Centered EEG Acquisition: cEEGrids for Transparent EEG

Abstract: Electroencephalography (EEG) is an important clinical tool and frequently used to study the brain-behavior relationship in humans noninvasively. Traditionally, EEG signals are recorded by positioning electrodes on the scalp and keeping them in place with glue, rubber bands, or elastic caps. This setup provides good coverage of the head, but is impractical for EEG acquisition in natural daily-life situations. Here, we propose the transparent EEG concept. Transparent EEG aims for motion tolerant, highly portable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
193
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 65 publications
6
193
0
2
Order By: Relevance
“…This revealed that the horizontal derivations FB(R) and FB(L) were the most informative for preserving sleep‐relevant information. This is similar to work presented in Bleichner, Mirkovic, and Debener (), where the significance of cEEGrid channel orientations for picking up far‐field electrical activity was discussed. In the present study, we exploited the electrode redundancy to obtain a reliable signal representation in all instances during sleep.…”
Section: Discussionsupporting
confidence: 86%
“…This revealed that the horizontal derivations FB(R) and FB(L) were the most informative for preserving sleep‐relevant information. This is similar to work presented in Bleichner, Mirkovic, and Debener (), where the significance of cEEGrid channel orientations for picking up far‐field electrical activity was discussed. In the present study, we exploited the electrode redundancy to obtain a reliable signal representation in all instances during sleep.…”
Section: Discussionsupporting
confidence: 86%
“…Many researchers have shown that EEG recordings from around the ear can reliably decode auditory attention (Bleichner & Debener, ; Debener, Emkes, De Vos, & Bleichner, ; Mirkovic et al., ). The success of the six‐channel near‐ear decoding presented here provides promise for applying these methods to cognitively steered hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ICs reflecting EKG based on prominent QRS complexes and regular eye artifacts were removed from cEEGrid-EEG data after visual inspection (see Bleichner and Debener, 2017). All EEG data was also specifically checked for ICs reflecting horizontal eye movements and relevant ICs were removed.…”
Section: Methodsmentioning
confidence: 99%